Information and communications technologies in low and middle-income countries: Survey results on economic development and health. Issue 4 (December 2016) - Quaglio, GianLuca; Dario, Claudio; Karapiperis, Theodoros; Delponte, Laura; Mccormack, Sarah; Tomson, Göran; Micheletti, Giorgio; Bonnardot, Laurent; Putoto, Giovanni; Zanaboni, Paolo
Abstract: Background: Despite the wide gap between the developed and developing world in terms of ICT access, ICT investment in low and middle-income countries (LMICs) has increased due to the rapid development of mobile services. However, the effects of ICTs in LMICs remain debatable. Methods: An online survey was conducted to collect feedback from experts. The questionnaire explored the role of ICTs in the economic development of LMICs, investigated the benefits and limits of e-health, and collected evaluations of past EU initiatives on future development policies. Structured interviews were also carried out with ten of the respondents. Results: One hundred and forty-five experts responded to the survey. Health and education were considered to be the two main areas where ICTs can support economic development. Poor infrastructure, lack of political support and human capital, and poor affordability were found to be the main obstacles. The shortcomings of donors in fostering the role of ICTs in LMICs development were identified as sustainability of interventions and lack of a coherent approach. The main benefits of e-health technologies in LMICs are their ability to facilitate health information and increase access to health care. Remote data collection, training for healthcare workers and education are the most effective m-health applications. Poor infrastructure and lack of equipment are considered the main barriers to the use of e-health in LMICs. Limited financial resources and lack of policy and regulatory frameworks might prevent the scaling up of e-health. Conclusions: The results of this survey can support decision makers and healthcare managers to better plan and implement ICTs in LMICs and make improved use of European resources for development. Highlights: Health and education are two main areas where ICTs can support economic development of LMICs. The main barriers hampering the use of ICTs in LMICs are the lack of infrastructures, affordability, lack of political support and human capital. The absence of adequate sustainability, an excessive technological approach and insufficient capacity building are the major factors responsible for the failure of ICT projects in LMICs. The strategy of many projects in the area of ICT for development fail to take into account key context variables. The main benefits of e-health technologies in LMICs were their ability to facilitate access to health information, health services, and training for health personnel.